Rubella infections among Libyan aborted women in Ajdabiya City- Eastern Libya - Souad Issa Rashwan (Journal of Libyan Academy Bani Walid, 2025)
The rubella virus is a potent teratogen that can lead to spontaneous abortion, stillbirths, and multiple birth defects known as congenital rubella syndrome (CRS) if infection occurs in the first trimester of pregnancy, especially in women without specific immune protection. The incidence of the viral infection is unknown among women who suffer from spontaneous abortion in most developing countries, and there are no specific treatments available to prevent complications. However, many developed countries have specific vaccination programs, and the disease has been eradicated , but it is still prevalent in some countries, especially developing countries. Rubella infection routine adult vaccinations have not yet been implemented in the EPI of Libya, and the prevalence of rubella antibodies among women continues to be reported in some Libyan cities, raising concerns about pregnancy outcomes and fetal health. So, the aim of the current study is to estimate the prevalence of rubella infections among aborted women in the city of Ajdabiya, to improve the introduced vaccination program and prevent abortion. Blood samples were collected from 42 aborted women, serum separated, and tested. The results showed that the total seropositivity of IgM (acute infection) and IgG levels of women were 19% and 71.4%, respectively. 26.2% of the study population were negative for IgM and IgG, suggesting a lack of immunization, either due to a lack of natural exposure or vaccination, which poses a risk to reproductive health. A third booster dose could be recommended to women who are planning to become pregnant at a sufficient time before pregnancy to avoid side effects. Also, a regular third booster dose could be recommended to women after puberty with continuous screening through a rubella survey program to prevent outbreaks of infection and abortion by combined efforts to develop an immunization program in this city and countrywide, and by contacting the relevant authorities to implement these programs.